AKT inhibition-mediated dephosphorylation of TFE3 promotes overactive autophagy independent of MTORC1 in cadmium-exposed bone mesenchymal stem cells. Issue 4 (3rd April 2019) - Pi, Huifeng; Li, Min; Zou, Lingyun; Yang, Min; Deng, Ping; Fan, Tengfei; Liu, Menyu; Tian, Li; Tu, Manyu; Xie, Jia; Chen, Mengyan; Li, Huijuan; et al.
ABSTRACT: Cadmium (Cd) is a toxic metal that is widely found in numerous environmental matrices and induces serious adverse effects in various organs and tissues. Bone tissue seems to be a crucial target of Cd contamination. Macroautophagy/autophagy has been proposed to play a pivotal role in Cd-mediated bone toxicity. However, the mechanisms that underlie Cd-induced autophagy are not yet completely understood. We demonstrated that Cd treatment increased autophagic flux and inhibition of the autophagic process using Atg7 gene silencing blocked the Cd-induced mesenchymal stem cell death. Mechanistically, Cd activated nuclear translocation of TFE3 but not that of TFEB or MITF, which contributed to the expression of autophagy-related genes and lysosomal biogenesis. Specifically, Cd decreased expression of phospho-AKT (Ser473). The reduction in AKT activity led to dephosphorylation of cytosolic TFE3 at Ser565 and promoted TFE3 nuclear translocation independently of MTORC1. Notably, Cd treatment increased the activity of PPP3/calcineurin, and pharmacological inhibition of PPP3/calcineurin with FK506 suppressed AKT dephosphorylation and TFE3 activity. These results suggest that PPP3/calcineurin negatively regulates AKT phosphorylation and is involved in Cd-induced TFE3-dependent autophagy. Modulation of the PPP3/calcineurin-AKT-TFE3 autophagic-lysosomal machinery may offer novel therapeutic approaches for the treatment of Cd-induced bone damage. Abbreviations: ACTB: actin: beta; AKT: thymoma viral proto-oncogene; AMPK: AMP-activated protein kinase; ATG: autophagy related; Baf A1: bafilomycin A1 ; Cd: cadmium; FOXO3: forkhead box O3; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MITF: melanogenesis associated transcription factor; MSC: mesenchymal stem sell; MTORC1: mechanistic target of rapamycin kinase complex 1; RPS6KB1: ribosomal protein S6 kinase: polypeptide 1; SGK1: serum/glucocorticoid regulated kinase 1; SQSTM1/p62: sequestosome 1;TFE3: transcription factor E3; TFEB: transcription factor EB; TFEC: transcription factor EC